ON THE ARTISTIC INTERPRETATION OF MUSICAL WORKS (ResearchJet Journal of Analysis and Inventions, 2023)
It is known that in the 21st century, the issue of high-quality teaching in the higher education system of art and culture of Uzbekistan is one of the urgent tasks. In this regard, it is clear that educational directions directly related to our national values, in particular, issues of achieving artistic interpretation in the performance of folk instruments, are in the center of attention. In fact, at present, the goals of nurturing the talent of our youth, forming their high-level aesthetic taste, and further improving their performance skills require the pedagogic staff to find answers to many questions. In particular, what is the advantage of choosing a way to educate a skilled performer, which methodological aspects should be paid special attention to, what tools should be used to achieve artistic interpretation in the process of studying musical works - these are among them. Among these questions, the issue of achieving artistic interpretation in performing specialties and specialties deserves special attention. Because in bringing a student to the level of a skilled performer, first of all, the tasks of forming his abilities to think independently, reach spiritual maturity, and acquire deep musical-historical and musical-theoretical knowledge are of great importance.